2020
DOI: 10.1108/et-09-2019-0204
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial characteristics amongst university students: insights for understanding entrepreneurial intentions amongst youths in a developing economy

Abstract: PurposeThis study focussed on investigating the impact of entrepreneurial characteristics on the entrepreneurial intention of university students in Nigeria.Design/methodology/approachThis research adopted a survey research design via a well-constructed questionnaire. The study's sample size consisted of 354 aspiring student entrepreneurs.FindingsThe result from the statistical analysis revealed that the entrepreneurial characteristics, especially risk tolerance, the need for achievement and the locus of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 45 publications
6
26
0
3
Order By: Relevance
“…In this context, intentions act as important mediating variables between starting a business and potential external influence (Peng et al , 2013; Yang, 2013; Krueger et al , 2000). Recently, Ibidunni et al (2020) have studied the impact of entrepreneurial characteristics on the entrepreneurial intentions of university students in Nigeria. Their results revealed that risk tolerance, the need for achievement and the locus of control are characteristics that significantly influence students' entrepreneurial intentions.…”
Section: The Entrepreneurial Intention – State Of the Artmentioning
confidence: 99%
“…In this context, intentions act as important mediating variables between starting a business and potential external influence (Peng et al , 2013; Yang, 2013; Krueger et al , 2000). Recently, Ibidunni et al (2020) have studied the impact of entrepreneurial characteristics on the entrepreneurial intentions of university students in Nigeria. Their results revealed that risk tolerance, the need for achievement and the locus of control are characteristics that significantly influence students' entrepreneurial intentions.…”
Section: The Entrepreneurial Intention – State Of the Artmentioning
confidence: 99%
“…Ajzen and Fishbein (1980) postulated that a consumer's intentions and actions could be predicted by attitudes. Based on the theory, the student satisfaction and loyalty assumes that student attitude influences the intentions to remain in the university ( Ibidunni et al. (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and international scholars have studied the entrepreneurial characteristics of new entrepreneurs. Specifically, Ayodotun et al (2020) investigated the entrepreneurial intention and entrepreneurial characteristics of young and middle-aged people in economic development. The statistical analysis results showed that formal university education was closely related to the cultivation of psychological education, innovation consciousness, and the entrepreneurial intention of young people.…”
Section: Regional Competitive Advantage Theory and Innovative Entrepreneurshipmentioning
confidence: 99%